2019
DOI: 10.1186/s13046-019-1352-3
|View full text |Cite
|
Sign up to set email alerts
|

Dropwort-induced metabolic reprogramming restrains YAP/TAZ/TEAD oncogenic axis in mesothelioma

Abstract: Background Over the past decade, newly designed cancer therapies have not significantly improved the survival of patients diagnosed with Malignant Pleural Mesothelioma (MPM). Among a limited number of genes that are frequently mutated in MPM several of them encode proteins that belong to the HIPPO tumor suppressor pathway. Methods The anticancer effects of the top flower standardized extract of Filipendula vulgaris (Dropwort) were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Accordingly, they are often well tolerated by patients and do not induce severe adverse events. Moreover, thanks to their chemical structure, they can concurrently impinge Lactobacillus Probiotic Preserves mucosal intestinal architecture [106,107] on several cellular signaling pathways thus affecting mucositis pathogenesis process at different levels, as well as negatively impacting on tumorigenic activities of cancer cells [109,111,112]. Actually, diverse natural products have been already tested and others are under investigation in active clinical trials.…”
Section: Natural Agentsmentioning
confidence: 99%
“…Accordingly, they are often well tolerated by patients and do not induce severe adverse events. Moreover, thanks to their chemical structure, they can concurrently impinge Lactobacillus Probiotic Preserves mucosal intestinal architecture [106,107] on several cellular signaling pathways thus affecting mucositis pathogenesis process at different levels, as well as negatively impacting on tumorigenic activities of cancer cells [109,111,112]. Actually, diverse natural products have been already tested and others are under investigation in active clinical trials.…”
Section: Natural Agentsmentioning
confidence: 99%
“…The in-silico analysis revealed that several targets triggered by miRNA-181a-5p and 193a-5p were involved in mesothelioma development. In particular, we found proteins involved in the regulation of pathways aberrantly activated in mesothelioma, such as MAPK, PI3K-Akt and mTOR signalling pathways [ 4 , 11 , 12 ], as well as the EGFR [ 13 ], Hippo [ 14 , 15 ], epithelial to mesenchymal transition [ 16 ] and NF-kappa B signalling pathways [ 17 , 18 ]. While miRNA-181-5p exerts an inhibitor regulation on those pathways, thereby eliciting a tumor-suppressor effect, miRNA 193-5p had an inverse role.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, verteporfin exhibits many undesirable effects that prevent its use in clinical practice. Another study showed that using the extract from the top flower of a medicinal plant, Dropwort, restrains the oncogenic activity of both YAP and TAZ through promoting ubiquitination in both “in vitro” and “in vivo” MPM models [ 261 ]. Additionally, peptide inhibitors that disrupt the interaction between TEAD and YAP/TAZ could represent a potential therapeutic option, as recently shown in gastric cancer [ 262 ].…”
Section: What Therapeutic Targets Among Hippo Pathway Members Should ...mentioning
confidence: 99%